Guest

if ax/cos A +by/sin A =a^2-b^2 and ax/cos^2 A- by cos A/sin^2 A=0 then prove that (ax)^2/3 + (by)^2/3 = (a^2-b^2)^2/3

if ax/cos A +by/sin A =a^2-b^2 and ax/cos^2 A- by cos A/sin^2 A=0 then prove that (ax)^2/3 + (by)^2/3 = (a^2-b^2)^2/3

Grade:10

1 Answers

Saurabh Koranglekar
askIITians Faculty 10335 Points
3 years ago
Dear student

Please write the question in standard notation using brackets

Regards

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free